Carbapenem-resistant Klebsiella pneumoniae infections in Chinese children: in vitro activities of ceftazidime-avibactam and aztreonam-avibactam against carbapenemase-producing strains in a two-center study - Ran, Xia; Chen, Xue; Wang, Cai; Wang, Haiping; Xie, Wei; Jing, Chunmei (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study assessed epidemiology characteristics, carbapenem-resistance genes, and drug resistance to ceftazidime-avibactam (CZA) and aztreonam-avibactam (AZA) in children with carbapenem-resistant Klebsiella Pneumoniae (CRKP) infections.MethodsA total of 363 non-repetitive CRKP strains were collected from children who underwent two tertiary children’s hospital between 1 January 2021 and 30 June 2024 in Chongqing and Kunming in Southwest China. Carbapenem resistance genes and antimicrobial susceptibility were analyzed. Basic clinical characteristics of the patients were obtained from medical records.ResultsblaNDM-5, blaNDM-1, and blaKPC-2 were the predominant carbapenemase genes; their detection rates were 35.8%, 30.3%, and 25.3%, respectively. Patients in the KPC-2-producing Klebsiella pneumoniae (KPC-KP) (median age, 90 days) were older than those producing NDM-1 and NDM-5 Klebsiella pneumoniae (NDM-KP) (median age, 37 days) (P < 0.05). The detection rate of NDM-KP in the neonatal unit was higher compared with KPC-KP (62.5% vs. 9.8%, P < 0.05), while the detection rate of NDM-KP in the intensive care unit (ICU) was decreased compared with KPC-KP (9.6% vs. 40.2%, P < 0.05). NDM-KP had lower resistance rates to aminoglycosides and fluoroquinolones than KPC-KP; the resistance rate of aminoglycosides and fluoroquinolones among NDM-KP and KPC-KP in Chongqing was increased compared with Kunming. The sensitivity rates of KPC-KP to CZA and NDM-KP to AZA were 100%, and the MIC50 of the CRKP to CZA and AZA were 2 μg/mL and 0.125μg/mL, respectively.ConclusionsThe epidemiological characteristics of Chinese children with CRKP infections, including the resistance genes and the antibiotic resistance of CRKP, exhibited significant variation between the two regions.KPC-KP strains had higher antimicrobial resistance in patients and thus should be given more attention in clinics and infection control.